Antichemotactic and Antifungal Action of the Essential Oils from Cryptocarya aschersoniana, Schinus terebinthifolia, and Cinnamomum amoenum. Issue 8 (12th July 2019) - Maciel, Ana J.; Lacerda, Caroline P.; Danielli, Letícia J.; Bordignon, Sérgio A. L.; Fuentefria, Alexandre M.; Apel, Miriam A.
Abstract: The purpose of this work was to determine the chemical composition and evaluate the antichemotactic, antioxidant, and antifungal activities of the essential oil obtained from the species Cryptocarya aschersoniana Mez, Cinnamomum amoenum (Ness & Mart .) Kosterm., and Schinus terebinthifolia Raddi, as well as the combination of C. aschersoniana essential oil and terbinafine against isolates of dermatophytes. Allo‐aromadendrene, bicyclogermacrene, and germacrene B were identified as major compounds in essential oils. The essential oil of C. aschersoniana shown 100 % inhibitory effect on leukocyte migration at the concentration of 10 μg/mL while S. terebinthifolia oil presented 80.1 % inhibitory effect at the same concentration. Only S. terebinthifolia oil possessed free‐radical‐scavenging activity which indicates its antioxidant capacity. The essential oils were also tested against fungal isolates of dermatophyte species ( Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis and Microsporum gypseum ), resulting in MIC ranging from 125 μg/mL to over 500 μg/mL. C. aschersoniana oil combined with terbinafine resulted in an additive interaction effect. In this case, the essential oil may act as a complement to conventional therapy for the topical treatment of superficial fungal infections, mainly because it is associated with an anti‐inflammatory effect. Abstract :